In vivo targeting of protein antigens to dendritic cells using anti‐DEC‐205 single chain antibody improves HIV Gag specific CD4+ T cell responses protecting from airway challenge with recombinant vaccinia‐gag virus - Loveline N. Ngu; Nadesh N. Nji; Georgia E. Ambada; Bertrand Sagnia; Carol Ngane Sake; Jules Colinc Tchadji; Ghislain Donald Njambe Priso; Abel Lissom; Thibau Flaurant Tchouangueu; Denis Manga Tebit; Alain Bopda Waffo; Chae Gyu Park; et al. (Immunity, Inflammation and Disease, 2019)
Abstract Introduction Targeting antigens to dendritic cells (DCs) in vivo via a DC‐restricted endocytic receptor, DEC205, has been validated to enhance immunity in several vaccine platforms. Particularly atttractive is selected delivery of proteins to DCs in vivo because it enables proteins to be more immunogenic and provides a cheaper and effective way for repeated immunizations. Methods In this study, we tested the efficacy of a single chain antibody to DEC205 (scDEC) to deliver protein antigens selectively to DCs in vivo and to induce protective immunity. Results In comparison to soluble Ovalbumin (OVA) antigen, when recombinant scDEC:OVA protein was injected subcutaneously (s.c.) into mice, the OVA protein was selectively presented by DCs to both TCR transgenic CD8+ and CD4+ T cells approximately 500 and 100 times more efficient than soluble OVA, respectively, and could persist for seven days following s.c. injection of the scDEC205:OVA. Similarly selective targeting of HIV Gag P24 to DCs in vivo using scDEC‐Gag protein plus polyICLC vaccine resulted in strong, long lasting, polyfuntional CD4+ T cells in mice which were protective against airway challenge by a recombinant vaccinia‐gag virus. Conclusion Thus targeting protein antigens to DCs using scDEC can be used either alone or in combination with other strategies for effective immunization.